2000
DOI: 10.1111/j.1749-6632.2000.tb05304.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Constant Estimation in Tropical Horse Tick, Anocentor nitens (Acari:Ixodidae)

Abstract: Experience has demonstrated that the exclusive use of acaricides as a control method against cattle ticks causes several problems, and is not totally effective. Other methods need to be added in order to achieve better and more profitable control of these parasites. Groups of 12 to 15 engorged ticks, bred on bovines, were individually incubated at six temperatures (T= 24, 26, 28, 30, 32, and 34°C) and four relatives humidities (RH= 100, 80, 75.5, and 70%), creating 24 variants. The onset of oviposition and ecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…During the autumn and winter months of the present study, preoviposition and egg incubation periods were longer, certainly because of the lower mean temperature on soil during these seasons of the years. This statement is supported by laboratory studies that demonstrated an inverse effect of temperature, regardless of relative humidity, on the duration of preoviposition and egg incubation periods of D. nitens (Despins, 1992;Bastos et al, 1996;de la Vega & Díaz, 2000).…”
Section: Discussionmentioning
confidence: 79%
“…During the autumn and winter months of the present study, preoviposition and egg incubation periods were longer, certainly because of the lower mean temperature on soil during these seasons of the years. This statement is supported by laboratory studies that demonstrated an inverse effect of temperature, regardless of relative humidity, on the duration of preoviposition and egg incubation periods of D. nitens (Despins, 1992;Bastos et al, 1996;de la Vega & Díaz, 2000).…”
Section: Discussionmentioning
confidence: 79%